1994
DOI: 10.1093/hmg/3.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis type I: identification of 8 novel mutations and determination of the frequency of the two common α-L-iduronidase mutations (W402X and Q70X) among European patients

Abstract: A group of 46 European patients with mucopolysaccharidosis type I (MPS I) was screened for mutations of the alpha-L-iduronidase gene. The 2 common nonsense mutations, W402X and Q70X, were identified in, respectively, 37% and 35% of mutant alleles. Considerable differences were seen in the frequency of these 2 mutations in patients from North Europe (Norway and Finland) and other European countries (mainly The Netherlands and Germany). In Scandinavia, W402X and Q70X account for 17% and 62% of the MPS I alleles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 0 publications
6
82
1
3
Order By: Relevance
“…These data are consistent with the previous Italian study where six common mutations were searched for (Gatti et al,1997). Italy has different mutation frequencies compared to other European countries: the G51D mutation has the highest frequency here (13.3%), but has only been found in one patient of German origin (Bunge et al, 1994). No other studies have reported this mutation in MPS-I patients.…”
Section: -1903del2mentioning
confidence: 60%
See 2 more Smart Citations
“…These data are consistent with the previous Italian study where six common mutations were searched for (Gatti et al,1997). Italy has different mutation frequencies compared to other European countries: the G51D mutation has the highest frequency here (13.3%), but has only been found in one patient of German origin (Bunge et al, 1994). No other studies have reported this mutation in MPS-I patients.…”
Section: -1903del2mentioning
confidence: 60%
“…W402X is the most common mutation in English-speaking countries, with an incidence of between 45-55 % in Australia, the UK and the USA (Scott et al, 1995). In Central Europe incidence is around 30% (Bunge et al, 1994), but in Spain this rises to 60% (Gort et al, 1998). The data for the Q70X mutation are consistent with a Scandinavian origin (60%; Bunge et al, 1994), from where it has spread to Southern Europe: 10% in Spain (Gort et al, 1999) and 15% in our study.…”
Section: -1903del2mentioning
confidence: 99%
See 1 more Smart Citation
“…There are three recognized MPS I clinical subgroups, which represent different points in a continuous clinical spectrum: Hurler, Hurler-Scheie, and Scheie syndromes. The majority of MPS I patients (up to 70%) present with Hurler syndrome, and have early onset and rapid disease progression (Bunge et al 1994;Gort et al 1998;Brooks 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The association of premature stop codon mutations with early onset and rapidly progressive Hurler syndrome is the result of an inability to synthesize a full-length polypeptide and the ensuing dire consequences on enzyme activity (Scott et al 1992b(Scott et al , 1993Brooks 2002). The two a-L-iduronidase gene (IDUA) premature stop codon mutations, Q70X and W402X, are the most common mutations in MPS I patients (Scott et al 1992a, b;Bunge et al 1994) and this skews the clinical spectrum towards Hurler syndrome.…”
Section: Introductionmentioning
confidence: 99%